A qualitative study on professional cognition and emotion of nursing students based on visual thinking theory (基于视觉思维理论的影视、听资料对护理学生专业认知和情感影响的质性研究) - BAI Jinlu (白金璐); LI Chunxiang (李春香); XU Hang (许航); LI Yan (李妍) (Association of Integrative Nursing, 2023)
Objective To investigate the influence of video and audio-visual materials based on visual thinking theory on nursing students' professional cognition and emotion, and to find methods to improve nursing students' professional cognition and strengthen positive emotion orientation, so as to provide basis for nursing curriculum reform. Methods The phenomenological method was used to conduct in-depth interviews with 14 nursing students in the school of Nursing of Henan University of science and Technology, and the data were analyzed by Colaizzi's 7-step method analysis method. Results The influence of video and audio-visual materials based on visual thinking theory on nursing students' professional cognition and emotion can be summarized into four themes: Deepening professional cognition; Improving learning enthusiasm; Deepening professional identity and nursing specialty; assertiveness of engaging in nursing specialty. Conclusion Nursing students have shortcomings, such as insufficient professional cognition, low professional learning enthusiasm and weak professional identity. Nursing teachers need to reform nursing courses by establishing video and audio-visual resource database to enhance nursing students' learning enthusiasm and professional identity. (目的 研究基于视觉思维理论的影、视听资料对护理学生的专业认知和情感的影响, 寻求提升护理学生专业认知、强化专业情感的方法, 为护理专业课程改革提供依据。方法 影视、听资料干预后对14名某高校本科护理学生进行深入访谈, 并运用Colaizzi 7步分析法对访谈资料分析。结果 观看影视、听资料后护理学生在专业认知和情感影响的质性资料可以归纳为四个主题: 专业认知加深、学习积极性提升、专业认同感加深、从事护理专业的信心更加坚定。结论 新入校的护理学生存在专业认知不足、学习积极性不高、专业认同感不强等问题, 需要护理教师通过建立有效的教学措施增强护理学生专业认识, 增加专业认同感, 从而提升专业的学习积极性和热爱护理专业。)